2021
DOI: 10.21203/rs.3.rs-222735/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating and modelling risk factors for primary postpartum haemorrhage among childbearing Women in the Northern Province of Rwanda: A Case Control Study

Abstract: Background: The vast majority of maternal deaths occur in Low- and Middle-Income Countries. Postpartum haemorrhage (PPH) remains a major global burden contributing to high maternal mortality and morbidity rates. Assessment of PPH risk factors should be undertaken during antenatal, intrapartum and postpartum periods for timely prevention of maternal morbidity and mortality associated with PPH. The aim of this study is to investigate and model risk factors for primary PPH in Rwanda. Methods: We conducted an obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(80 reference statements)
2
0
0
Order By: Relevance
“…Similarly, consistent with a study conducted in Ethiopia [ 19 ] and Afghanistan [ 39 ], the result of the current study demonstrated that antepartum haemorrhage in recent pregnancy and vaginal or cervical laceration was a risk factor for the incidence of PPPH. This study also found retained placenta to be a risk factor for the incidence of PPPH, which was similar to a study conducted in Rwanda [ 40 ]. This study identified two critical factors aligned to the “Three Delays” model [ 13 ], for maternal morbidity in northwest Ethiopia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, consistent with a study conducted in Ethiopia [ 19 ] and Afghanistan [ 39 ], the result of the current study demonstrated that antepartum haemorrhage in recent pregnancy and vaginal or cervical laceration was a risk factor for the incidence of PPPH. This study also found retained placenta to be a risk factor for the incidence of PPPH, which was similar to a study conducted in Rwanda [ 40 ]. This study identified two critical factors aligned to the “Three Delays” model [ 13 ], for maternal morbidity in northwest Ethiopia.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, most of the factors associated with the occurrence of PPPH among women in northwest Ethiopia were similar to those found in several other studies undertaken in low-resource settings [ 18 , 19 , 25 , 39 , 40 ]. In line with studies conducted in Ethiopia [ 18 , 19 , 25 ], this study shows an association between the age of women (≥35 years), instrumental-assisted birth as well as longer than 24 hours of labour and PPPH.…”
Section: Discussionsupporting
confidence: 88%